Evaluation of telemonitoring of continuous positive airway pressure therapy in obstructive sleep apnoea syndrome: TELEPAP pilot study. (July 2021) - Fernandes, Manuel; Antunes, Catarina; Martinho, Cristina; Carvalho, João; Abreu, Tiago; Oliveira, Ana; Pinto, Paula; Bárbara, Cristina
Introduction: Continuous positive airway pressure is an effective treatment for obstructive sleep apnoea syndrome. However, positive airway pressure compliance rates are disappointingly low, so effective interventions are needed to improve compliance in sleep apnoea. Telemonitoring has been used to improve compliance, but results have been inconsistent. This study aimed to determine outcomes of telemonitoring positive airway pressure compliance and efficacy data compared to usual care and phone-call care. Methods: Randomized controlled study in which 51 patients (82.4% male; between 25 and 78 years), diagnosed with moderate to severe obstructive sleep apnoea were consecutively randomized to usual care, weekly phone-call care or telemonitored care with the use of Restraxx™. All patients were submitted to a comprehensive educational programme during positive airway pressure adaptation. Patients were followed for the first four weeks of treatment with automatic positive airway pressure (AutoSet Spirit S8®; ResMed), and compliance and efficacy data were analyzed. Results: Telemonitored care group used automatic positive airway pressure an average of 5.0 ± 1.8 hours/night, usual care patients 5.1 ± 2.5 hours and phone-call care patients 3.9 ± 2.6 hours. The residual Apnoea--Hypopnoea Index was 5.3 ± 3.0 in telemonitored care, 5.0 ± 2.5 in usual care and 5.6 ± 3.8 in phone-call care. No statistically significant differences were found between groups regarding positive airway pressure compliance or efficacy ( p  = 0.296 and p  = 0.825, respectively). Discussion: In the presence of a comprehensive educational programme during positive airway pressure adaptation, telemonitoring patients did not show benefits concerning compliance and efficacy. A larger follow-up period is needed to evaluate the long-term results of a telemonitoring programme.